DAMPAK PEMBAYARAN COD TERHADAP KEPUTUSAN PEMBELIAN DAN KEPERCAYAAN KONSUMEN SHOPEE EXPRESS: Cash on Delivery, keputusan pembelian, kepercayaan konsumen - Fajar Riandy; Meisa Fitri Nasution (LPPM STIEM BONGAYA, 2026)
This study analyzes the impact of the Cash on Delivery (COD) payment system on purchase decisions and consumer trust in Shopee Express services in Bagan Batu City, Rokan Hilir Regency. A quantitative method was employed using a Structural Equation Modeling – Partial Least Square (SEM-PLS) approach with SmartPLS software. The sample consisted of 100 respondents selected through purposive and accidental sampling techniques. Data were collected using a Likert-scale questionnaire. The results indicate that the COD payment system has a positive and significant effect on purchase decisions (coefficient = 0.943; p = 0.000) and on consumer trust (coefficient = 0.902; p = 0.000). Purchase decisions also show a positive and significant effect on consumer trust (coefficient = 0.918; p = 0.000). Mediation analysis reveals that purchase decisions significantly mediate the effect of the COD payment system on consumer trust. These findings suggest that the implementation of COD payment enhances consumers' sense of security in transactions, encourages purchase decisions, and strengthens consumer trust toward e-commerce platforms